My Korean deli : risking it all for a convenience store - Howe, Ben Ryder (Picador., 2012)
A former senior editor of "The Paris Review" recounts his participation in a family effort to buy and run a Korean convenience store for his in-laws, a pursuit that raised issues about work and family while he shuttled between two divergent cultural arenas.